Spontaneous Intra-Gastric Walled-Off Pancreatic Necrosis Rupture - Papadimitriou, Nikolaos; Robotis, John; Rokkas, Theodoros (JOP. Journal of the Pancreas, 2014)
No abstract available. Image: Walled-off pancreatic necrosis interior.